Room temperature fabrication of transparent p-NiO/n-ZnO junctions with tunable electrical properties. (March 2018) - Wang, Y.B.; Wei, X.H.; Chang, L.; Xu, D.G.; Dai, B.; Pierson, J.F.; Wang, Y.
Abstract: Transparent p-n heterojunctions composed of p-NiO and n-ZnO thin films have been fabricated on indium-tin-oxide (ITO)-coated glass substrates at room temperature by magnetron sputtering. Various oxygen flow rates have been employed to grow the NiO thin films, yielding the tunable resistivity of NiO layers. These p-n junctions exhibit clear rectifying current-voltage characteristics. Moreover, their electrical properties can be effectively tuned by the oxygen flow rate to synthesize NiO layers in these junctions. NiO layer with closely perfect stoichiometry and quite high resistivity produces better performance in these p-n junctions, including the small threshold voltage and ideality factor, as well as high rectifying ratio. The evolution tendency of threshold voltage as a function of the resistivity of NiO is qualitatively discussed. Highlights: Transparent p-NiO/n-ZnO heterojunctions have been fabricated at room temperature. The properties of junctions can be tuned by the oxygen flow rate to synthesize NiO layer. The threshold voltage of 0.95 V has been attained in the junction with a high resistivity NiO.